Development of an in vivo DNA Cloning Procedure for Bacteria - Chain, Patrick (My University, 1998)
In this thesis, we describe the development of a method to delete and to clone specific large regions from the 1700 kilobase pExo megaplasmid of Rhizobium meliloti. In principal, the region to be cloned is flanked by FRT sites, which direct site specific recombination by the Flp recombinase. Targeting constructs were designed to include part of the IS50 from Tn5, the FRT site, an origin of transfer (oriT), and a replication origin from RK2 or the F plasmid. These constructs were directed to known Tn5-derivative insertion sites in the pExo megaplasmid. A plasmid which expresses the Flp recombinase constitutively in R. meliloti was made, and the transfer of this plasmid to FRT-flanked megaplasmid regions was shown to result in the deletion of the intervening DNA. We demonstrated that the pExo megaplasmid DNA regions could be captured in Escherichia coli, however in this case, the megaplasmid excision event appears to be directed by the oriT sites rather than the FRT sites. We present strong evidence that a specific 50 kb region contains the oriV of the pExo megaplasmid; R. meliloti strains deleted for this region could not be isolated, and this region was found to replicate autonomously in Agrobacterium tumefaciens. Preliminary sequence analysis has revealed strong homology within this region to genes encoding the RepABC replication proteins of several Rhizobium and Agrobacterium plasmids.
Development of an in vivo DNA Cloning Procedure
Keywords: development; in vivo; DNA Cloning; DNA Cloning Procedure; bacteria